2010
DOI: 10.1111/j.1442-9071.2010.02209.x
|View full text |Cite
|
Sign up to set email alerts
|

Aciclovir‐resistant herpes keratitis

Abstract: Herpes simplex virus (HSV) keratitis is a common cause of ocular morbidity. Resistance to aciclovir is probably under recognized. We describe three cases of aciclovir-resistant herpes simplex virus keratitis treated with systemic foscarnet and present a review of the pharmacological options available to manage this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The triphosphate forms of these analogues selectively inhibit the viral DNA polymerase (DNA pol) activity. After more than three decades of ACV administration, drug-resistant HSV isolates are rarely found in immunocompetent subjects (0.1–0.7%) but more frequently recovered from immunocompromised patients (4–14%) [12, 34, 36, 47]. HSV resistance to ACV generally arises as a result of mutations in viral thymidine kinase and in a lesser number from mutations in the viral DNA pool [19, 38].…”
Section: Introductionmentioning
confidence: 99%
“…The triphosphate forms of these analogues selectively inhibit the viral DNA polymerase (DNA pol) activity. After more than three decades of ACV administration, drug-resistant HSV isolates are rarely found in immunocompetent subjects (0.1–0.7%) but more frequently recovered from immunocompromised patients (4–14%) [12, 34, 36, 47]. HSV resistance to ACV generally arises as a result of mutations in viral thymidine kinase and in a lesser number from mutations in the viral DNA pool [19, 38].…”
Section: Introductionmentioning
confidence: 99%
“…Virological resistance is one of the reasons for therapeutic unresponsiveness in suspected herpetic keratitis, a dilemma that may lead to the selection of an alternative antiviral (Hlinomazová 2010). If resistant ocular HSV strains continue to emerge (Choong 2010; Hlinomazová 2010) the applicability of this review may need to be modified.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that a single amino acids change in primase protein with no change in the UL5 helicase leads to moderate resistance while single change in UL5 helicase results in co-resistance to both agents. [39] A source of worry is cross resistance in antiviral therapy; [40] a study by Moira et al, showed that acyclovir resistant to HSV also confers resistant to the same agent in HSV/HIV co-infection. The resistant associated with HIV was due to mutation in the reverse transcriptase [41] while another studies established cross resistance in ACV-resistant strain and brivudin and penciclovir as well as foscarnet.…”
Section: Mechanism Of Antiviral Drug Resistancementioning
confidence: 98%